Fire Brigades Union women conference delegates, 1943 (1943)
1943 1939-1945 "Fire Brigades Union women conference delegates, 1943" [HFR0038], 1943 This photo shows women delegates attending the FBU annual conference 'austerity' dinner. Herbert Morrison, Ellen Wilkinson and Anne Loughlin [centre in check jacket] also attended the dinner. Behind her are Marjorie Herd [with spectacles], National Women's Organiser, and Constance Tudor-Hart, Executive Council.